Can you swim the Bering Sea? - Iversen, Angus.; National Institute for Occupational Safety and Health. Division of Safety Research.
DHHS publication no. (NIOSH) 2014-107 If you can swim the Bering Sea, you're a better man than me. AND YOU ARENT. – Angus Iversen Today’s low-profile PFDs are comfortable, don’t tangle in gear and extend survival time in the water. Choose yours at livetobesalty.org. Then make it part of your standard on-deck gear.Live to be Salty is a multi-media health communication intervention developed by the National Institute for Occupational Safety and Health and our partners in an effort to reduce drownings, by promoting the use of PFDs on board commercial fishing vessels. Live to be Salty means to take steps that will lead to a long and productive fishing career. Live to be the Old Salt everyone looks to for advice by setting a good example for your crew and others. PFDs have come a long way in the last decade and many of the myths associated with them simply aren’t true. There are comfortable PFDs available on the market that you can wear 100% of the time on deck. PFDs that don’t snag on gear, don’t overheat you, and won’t restrict your movement. We hope to spread that word and save lives. Featuring quotations from the fictional "old salt" Angus Iversen. CDC-1099_posters_v5.indd 1